Physicochemical interactions between polyaniline and graphene oxide: the reasons for the stability of their chemical structure and thermal properties - Gandara M. (2021)
© 2021 Elsevier LtdSeveral works are reported in the literature on the use of a conducting polymer such as polyaniline (PANI) and its combination with graphene oxide (GO). Graphene derivatives have an important contribution to improve the electrochemical performance of charge transfer and polarization of the polymer in energy storage cells. To understand the chemical phenomena in PANI–GO interaction, this article presents the relationships of the thermal, chemical, and morphostructural properties of this composite material. This synergistic effect between the materials is responsible for performance enhancing. Therefore, in this work, after PANI electrosynthesis on carbon fiber and further dipping of GO, Field Emission Gun, Raman spectroscopy, X-Ray Excited Electron Photon Spectroscopy, Fourier-transform infrared spectroscopy, X-ray diffraction, Differential Scanning Calorimetry, and thermogravimetric techniques were used to characterize these materials. GO tends to stabilize the molecular structure of PANI in its protonation/deprotonation and redox processes. Through thermal analysis, it was possible to observe that GO increases the stability of PANI at higher temperatures, minimizing mass loss rates and changing the polymer's glass transition temperature. And when observing the structure of the material under the influence of temperature, the GO kept the structures practically unaltered (PANI crystallographic orientation) up to 150 °C. These facts highlight important material stability data to be considered in energy storage system applications.